The The Influence Of Infrastructure, Learning Methods On Student Achievement Through Student Learning Motivation During The COVID-19 Pancemic at SMK Negeri 9 Jakarta - Refanny Mayta Novilia; Setyo Riyanto (Dinasti Publisher, 2023)
Through examining student learning motivation, this study seeks to determine the impact of online learning infrastructure and techniques on student learning achievement. The population of this study is students at SMK Negeri 9 Jakarta, with a sample size of 150 students. The data analysis method used Structural Equation Model-Partial Least Square (SEM-PLS). The findings of this study show that student achievement is not directly affected. The strategy of online learning facilities and infrastructure significantly influences students' enthusiasm for learning. Students learning achievement is directly affected by their enthusiasm to learn. Although the online learning infrastructure is not like the offline learning approach, it indirectly impacts student achievement through students' motivation to learn. The implications of this research are discussed in the article.